2021
DOI: 10.3390/rs13152932
|View full text |Cite
|
Sign up to set email alerts
|

Using Multi-Temporal Satellite Data to Analyse Phenological Responses of Rubber (Hevea brasiliensis) to Climatic Variations in South Sumatra, Indonesia

Abstract: Land surface phenology derived from satellite data provides insights into vegetation responses to climate change. This method has overcome laborious and time-consuming manual ground observation methods. In this study, we assessed the influence of climate on phenological metrics of rubber (Hevea brasiliensis) in South Sumatra, Indonesia, between 2010 and 2019. We modelled rubber growth through the normalised difference vegetation index (NDVI), using eight-day surface reflectance images at 250 m spatial resoluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 92 publications
0
21
0
Order By: Relevance
“…It was shown that the phenological SOS, EOS, and LOS were closely related to such deviations as extreme precipitation and increased temperature. The increase in the temperature by 1 °C led to an increase in SOS by ~25 days and EOS -by ~14 days (Azizan, 2021).…”
Section: Discussionmentioning
confidence: 97%
“…It was shown that the phenological SOS, EOS, and LOS were closely related to such deviations as extreme precipitation and increased temperature. The increase in the temperature by 1 °C led to an increase in SOS by ~25 days and EOS -by ~14 days (Azizan, 2021).…”
Section: Discussionmentioning
confidence: 97%
“…As a result, to reduce the impact of weather fluctuations on the analyses, all images were captured during the dry season. It is recommended that images be from the same recording period to reduce variations from image to image caused by sun angle, soil moisture, atmospheric conditions, and differences in vegetation phenology (Azizan et al, 2021;Verstegen et al, 2019). (Gashaw et al, 2017;Ruben et al, 2020).…”
Section: Datamentioning
confidence: 99%
“…Most of the studies identified canopy density based on the vegetation index on multispectral satellite images. In Azizan's research [10], a phenology analysis of canopy density was performed using NDVI on Sentinel-2 imagery and MODIS temporally. Meanwhile, Razak's research [11] used several vegetation indices such as NDVI, EVI, LAI, and RGRI on Landsat ETM imagery to detect canopy density as a basis for time seriesphenology analysis.…”
Section: Introductionmentioning
confidence: 99%